2018
DOI: 10.1007/s11158-018-09406-z
|View full text |Cite
|
Sign up to set email alerts
|

The Right to be Publicly Naked: A Defence of Nudism

Abstract: Many liberal democracies have legal restrictions on nudism. This article argues that when public nudity does not pose a health threat (which it seldom does), such restrictions are unjust. To vindicate this claim, I start by showing that there are two weighty interests served by the freedom to be naked in public. First, it promotes individual well-being; not only can nudist activities have great recreational value, recent studies have found that exposure to non-idealised naked bodies has a positive impact on bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As well as the direction of the effect, prior research has not yet identified potential mediators or mechanisms that could explain it. One suggestion made by naturist organisations themselves is that the effect occurs due to a recalibration of one's perceptions of normal bodies and thus of one's own attractiveness compared to other people (British Naturism, 2016;de Vries, 2018). Some prior research supports this suggestion.…”
Section: Why Would Nakedness Improve Body Image?mentioning
confidence: 99%
“…As well as the direction of the effect, prior research has not yet identified potential mediators or mechanisms that could explain it. One suggestion made by naturist organisations themselves is that the effect occurs due to a recalibration of one's perceptions of normal bodies and thus of one's own attractiveness compared to other people (British Naturism, 2016;de Vries, 2018). Some prior research supports this suggestion.…”
Section: Why Would Nakedness Improve Body Image?mentioning
confidence: 99%
“…Naturism (or nudism) can be defined most simply as the practice of public or communal nudity (de Vries, 2018). In general, naturism combines the behaviour of being naked in the company of people other than one's intimate partner (Carr‐Gomm, 2012; Deschenes, 2016), with the assumption that the activity does not have, or at least is not limited to, sexual connotations (Smith, 2007; Smith & King, 2009; West & Geering, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…), with thousands of individuals cycling naked through cities in order to highlight the vulnerability of cyclists [17]. In fact, polls conducted by Ipsos-Mori suggest that around 25% of individuals in Britain have taken part in some kind of nudist activity (e.g., nude sunbathing) between 2001 and 2011 [18].…”
Section: Introductionmentioning
confidence: 99%